2017
DOI: 10.3892/or.2017.6150
|View full text |Cite
|
Sign up to set email alerts
|

miR-141-3p suppresses proliferation and promotes apoptosis by targeting GLI2 in osteosarcoma cells

Abstract: MicroRNAs (miRNAs) have been reported as key regulators in numerous diseases including osteosarcoma. The function of microRNA-141-3p (miR-141-3p) and whether this function is achieved by regulation of GLI family zinc finger 2 (GLI2) in osteosarcoma remain unclear. In the present study, we found decreased expression of miR-141-3p, but increased expression of GLI2 in osteosarcoma tissues and cell lines. In addition, we demonstrated a negative correlation between miR-141-3p and GLI2. Furthermore, we revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The procedure was carried out as previously described . In briefly, HOS and 143B cells after different MALAT1, HDAC4, or miR‐140‐5p intervene were seeded on coverslips and incubated for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was carried out as previously described . In briefly, HOS and 143B cells after different MALAT1, HDAC4, or miR‐140‐5p intervene were seeded on coverslips and incubated for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was carried out as previously described. 30 In briefly, HOS and 143B cells after different MALAT1, HDAC4, or miR-140-5p intervene were seeded on coverslips and incubated for 48 hours. All coverslips were fixed using of 4% paraformaldehyde for 30 minutes and then were permeabilized with 0.1% Triton X-100 for 2 minutes on ice.…”
Section: Terminal Deoxynucleotidyl Transferase (Tdt) Dutp Nick-end mentioning
confidence: 99%
“…30 miR-141-3p suppresses cell PLF and enhances APS by targeting GLI2 in osteosarcoma. 31 Importantly, miR-141-3p expression is down-regulated during the progression of GC, 32 expressing that miR-141-3p primarily exerts tumor-suppressive effect in GC. Accumulating researches reveal that lncRNAs work on miRNAs via serving as ceRNA and competitively inhibit miRNAs as molecular sponges.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-141 was found to be overexpressed during senescence as a result of epigenetic regulation, which may lead to reduced tissue regeneration capacity and a decline in physiological functions 39 . Some studies have argued that downregulation of miR-141 could increase the proliferation of osteosarcoma cells and colorectal cancer SW480 cells 40,41 . In addition, it has been reported that upregulating miR-141-3p suppresses the invasion and migration of prostate cancer cells in vitro 42 .…”
Section: Discussionmentioning
confidence: 99%